Nanotechnology-Based Approaches for Voriconazole Delivery Applied to Invasive Fungal Infections - de Almeida Campos, Laís; Fin, Margani Taise; Santos, Kelvin Sousa [UNESP]; de Lima Gualque, Marcos William [UNESP]; Freire Cabral, Ana Karla Lima [UNESP]; Khalil, Najeh Maissar; Fusco-Almeida, Ana Marisa [UNESP]; Mainardes, Rubiana Mara; Mendes-Giannini, Maria José Soares [UNESP] (MDPI, 2023)
Invasive fungal infections increase mortality and morbidity rates worldwide. The treatment of these infections is still limited due to the low bioavailability and toxicity, requiring therapeutic monitoring, especially in the most severe cases. Voriconazole is an azole widely used to treat invasive aspergillosis, other hyaline molds, many dematiaceous molds, Candida spp., including those resistant to fluconazole, and for infections caused by endemic mycoses, in addition to those that occur in the central nervous system. However, despite its broad activity, using voriconazole has limitations related to its non-linear pharmacokinetics, leading to supratherapeutic doses and increased toxicity according to individual polymorphisms during its metabolism. In this sense, nanotechnology-based drug delivery systems have successfully improved the physicochemical and biological aspects of different classes of drugs, including antifungals. In this review, we highlighted recent work that has applied nanotechnology to deliver voriconazole. These systems allowed increased permeation and deposition of voriconazole in target tissues from a controlled and sustained release in different routes of administration such as ocular, pulmonary, oral, topical, and parenteral. Thus, nanotechnology application aiming to delivery voriconazole becomes a more effective and safer therapeutic alternative in the treatment of fungal infections.
Keywords: antifungals; fungal infections; nanoparticles; sustained drug release